PEMILIHAN SATWA PRIORITAS DI SUAKA MARGASATWA PALIYAN - , Nurrochmah Wisudhaningrum; , Dr. Satyawan Pudyatmoko, S.Hut.,M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Paliyan Wildlife Sanctuary has been designed to protect the habitat of long-tailed monkeys (Macaca fascicularis). In the initial condition of appointment, Paliyan Wildlife Sanctuary was damaged by looting. This ecosystem damage made Paliyan Wildlife Sanctuary different from other wildlife preserves which were appointed in relatively good condition of ecosystem. Long-tailed monkey in Paliyan Wildlife Sanctuary is considered a pest by the community. To further optimize the function of the area, it is necessary to select priority species which ecologically appropriate and supported by the community. Priority species is expected to be a direction in the management strategies and wildlife management plan which is more effective, efficient and comprehensive to achive the aim of the area management. The purpose of this study are to determine priority species for Paliyan Wildlife Sanctuary using Analytical Hierarchy Process method and to find out surrounding communities perception toward the function of Paliyan Wildlife Sanctuary in wildlife conservation. Analytical Hierarchy Process method was used to select the priority species with multi-criteria analysis. The strength of this process lied in its comprehensive design, by using quantitative and qualitative data logic. Likert Scale was used to measure community perception using scoring analysis technique. Species preservation criteria was used to select priority species (weight 0,52), ecological function (weight 0,434) and socio-economic interest (weight 0,213). The three criteria were outlined in 8 indicators and 10 sub-indicators. The highest score for priority species of aves was Gallus varius (Green Junglefowl) : 7,347, insect was Oecophylla sp (Rang-rang ant) : 5,685